The circuit designer's companion - Wilson, Peter (Newnes, 2011)
The third edition of this classic work on circuit design gives engineers the understanding and practical know-how to produce optimized, reliable, cost-effective electronic circuits. It bridges the gap between the theoretical learning that most university courses provide and the practical knowledge and application that comes from years of experience. Topics covered include analog and digital circuits, component types, power supplies and printed circuit board design. This new edition is updated with material on design tools and communication devices, high-speed digital circuit design, simulation methods and testing, as well as new coverage of the latest advances in electronics since the previous edition published. This third edition includes new coverage of: design tools and communication devices FPGAs (field-programmable gate arrays) SOICs (small outline integrated circuits) high-speed digital circuit design testing: DFT, AOI, AXI and other test methods CE marking and electrostatic discharge circuit simulation methods An invaluable companion for circuit designers and practicing electronics engineers - gives best practices, design guidelines and engineering knowledge gleaned from years of experience Includes practical, real-world considerations for components, PCBs, manufacturability, reliability and cost, enabling engineers to design and troubleshoot faster, cheaper and more effectively Contains new material on design tools and communication devices, high-speed digital circuit design, simulation methods and testing.